2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609530
|View full text |Cite
|
Sign up to set email alerts
|

Normalized power variance change between pre-ictal and ictal phase of an epilepsy patient using NAT analysis: A case study

Abstract: Variance of state variables shifts due to phase-instability and may serve as an early-warning signal of phase transition of complex systems such as an epileptic seizure of brain cortical activity. Neuronal Activity Topology (NAT) analysis calculates a normalized-power-variance (NPV) of electroencephalogram (EEG) data in each frequency band to obtain relative values comparable among different power states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…In the current implementation, the solution space consists of 6,239 voxels in the cortical grey matter at 5 mm spatial resolution, using a realistic head model [50] with the MNI152 template [51]. eLORETA has been widely used to explore cortical electrical activities, and its validity has been proved in healthy subjects and neuropsychiatric patients [19-21, 52, 53]. Pascual-Marqui et al [23] also showed the property of correct localization of eLORETA with human EEG data during various sensory stimulations even in the presence of structured noise.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current implementation, the solution space consists of 6,239 voxels in the cortical grey matter at 5 mm spatial resolution, using a realistic head model [50] with the MNI152 template [51]. eLORETA has been widely used to explore cortical electrical activities, and its validity has been proved in healthy subjects and neuropsychiatric patients [19-21, 52, 53]. Pascual-Marqui et al [23] also showed the property of correct localization of eLORETA with human EEG data during various sensory stimulations even in the presence of structured noise.…”
Section: Methodsmentioning
confidence: 99%
“…Exact low-resolution brain electromagnetic tomography (eLORETA) is a linear inverse solution that reconstructs cortical electrical activity from the scalp EEG data with correct localization [19-23]. Thus, eLORETA with EEG data has been widely used in neuroscience research [19, 20, 24-26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike fMRI, which measures hemodynamic changes that occur in response to cortical activity, neurophysiological techniques, such as EEG and MEG measure cortical electrical/magnetic activity directly and noninvasively with a high temporal resolution (1–2 ms) (Canuet et al, 2011 ). Thus, EEG has been widely used in clinical practice to support clinical diagnosis and management of neuropsychiatric diseases such as epilepsy, disturbance of consciousness and dementia, and also in neuroscience to investigate cortical electrical activities and functions (Ishii et al, 1999 ; Canuet et al, 2011 ; Kurimoto et al, 2012 ; Aoki et al, 2013a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is an urgent issue to find predictive factors for the surgical outcome. In a previous study, in order to investigate the mechanisms of functional recovery, we performed normalized power variance (NPV) analysis, which is a sensitive measure of the instability of cortical electrical activity 7 , on electroencephalography (EEG) data before and after CSF tapping, a procedure that drains a small volume of CSF (30 ml) by lumbar puncture. A striking finding was that cortical functional recovery induced by CSF tapping was associated with NPV changes.…”
mentioning
confidence: 99%